Consumer Satisfaction using Medical Masks and Cloth Masks as Affected by Price Perceptions and Product Attributes in Tampan District of Pekanbaru City - Sainatunnisak, Nurul; Alwie, Alvi Furwanti; Promalessy, Rika (Program Pascasarjana, Universitas Riau, 2022)
This study was conducted to determine the effect of price perceptions and product attributes of medical and cloth mask users on consumer satisfaction in the Tampan district of Pekanbaru city. This research employs quantitative methods and both primary and secondary data. This study's population included everyone in the Tampan sub-district. The snowball sampling method was used on a non-probability side, with each 100 respondents wearing medical and cloth masks. The results of this study indicate that price perception significantly affects consumer satisfaction when using medical masks and cloth masks in the Tampan district of Pekanbaru city. Product attributes have a significant effect on consumer satisfaction when using medical masks and cloth masks in the handsome district of Pekanbaru city. Price perception and product attributes simultaneously have a significant effect on consumer satisfaction when using medical masks and cloth masks in the Tampan district of Pekanbaru city.